Methylation Profile of HOXA 11 Gene in Eutopic Endometrium on Endometriosis Patient with Infertility - Natadisastra, Muharam; Yuwono, Valencia; Febri, Ririn; Asmarinah, Asmarinah (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the HOXA11 gene profile on endometriosispatients with infertility in Indonesia.Methods: This cross sectional study was conducted in Dr. CiptoMangunkusumo Hospital from July 2015- June 2016. The subjectswere endometriosis patients with infertility who have beenconfirmed histopathological. The control group was taken fromnon-endometriosis and fertile patients. Eutopic endometriumsamples were taken and examined for the methylation of HOXA 11gene.Results: Both groups consist of six patients. The difference ofmethylation of HOXA 11 gene between those two groups isstatistically significant (p=0.03). There was hyper methylation inendometriosis group.Conclusion: There is a hyper methylation of HOXA 11 gene ineutopic endometrium of endometriosis patients with infertility.Thus, possibly can explain the poor endometrial receptivityin endometriosis patient and give a broad research area inepigenetic therapy of endometriosis.[Indones J Obstet Gynecol 2018; 6-2: 110-113]Keywords: endometriosis, epigenetic, HOXA 11, infertility,methylation